Transformation mapping of the regulatory elements of the ecdysone-inducible P1 gene of Drosophila melanogaster. - Maschat, F.; Dubertret, M.L.; Lepesant, J.A. (Molecular and Cellular Biology, 1991)
The transcription of the P1 gene is induced by 20-hydroxyecdysone in fat bodies of third-instar larvae. Germ line transformation showed that sequences between -138 to +276 contain elements required for a qualitatively correct developmental and hormonal regulation of P1 transcription. Sequences from -138 to -68 are essential for this expression.